Fostering innovative behaviour: does work engagement and leader humility matter?. (1st September 2021) - Abbas, Wasim; Wu, Weiwei; Amin, Hina
The purpose of this research is, first, to identify the role of work engagement in the relationship between perception of justice and innovative behaviour in health organisations, and second, to investigate whether the leader moderates the mediating relationship between the aforementioned constructs at different levels. For this cross-sectional study, a pen and paper questionnaire survey method was used to collect data from registered nurses working in tertiary care public hospitals. Tested through the PROCESS macro, empirically assessed hypotheses show the distinct mediating role of work engagement, moderating role of leader humility, and a moderated mediated relation conjointly. The results show that perceived organisational justice positively impacts innovative behaviour through work engagement. Leader humility amplifies the positive relationship between engaged nurses and their innovative behaviour, and positively moderates the mediated relation between perceived organisational justice and innovative behaviour. The study concludes that public healthcare organisations should introduce impartial policies, provide clear instructions, and assure fair measures to maintain equity and equality in the workplace. Hospitals should devise systematic strategies to inculcate work engagement among nurses. Hospitals should nurture doctors by providing training and developmental programs to adopt humility in their leadership roles.